Abrupt climate change in arid central Asia during the Holocene: A review - Liu, Xiaokang; Chen, Jianhui; Chen, Shengqian; Wang, Haipeng; Huang, Wei; Feng, Song; Chen, Fahu (Earth-science reviews, 2023)
Unlike the long-term (e.g., Earth orbital-scale) climatic trend, abrupt climate changes in westerlies-dominated arid central Asia (ACA) during the Holocene remain unclear. We present the first comprehensive synthesis of centennial-scale climatic events in this region, based on nine rigorously-selected Holocene paleoclimatic records. The results show that mega-regional abrupt climate events were consistently recorded during the middle to late Holocene: five wet events (around 6.5 ka BP (thousand years before present), 4.7 ka, 3.3 ka, 1.8 ka, and 0.4 ka), and five dry events (around 7.6 ka, 5.3 ka, 3.9 ka, 2.6 ka, and 1.1 ka). Strikingly, such mega-regional climatic events were rarely indicated in the records before ∼5.5 ka, in contrast to the frequent alternation of wet-dry events afterwards. This pattern of mega-regional wet and dry events, although unevenly distributed in time, is ascribed to the intensification and southward movement of the westerlies since the late middle Holocene, which favored the establishment of climatic teleconnections across the entire region. By comparing climatic events in ACA with classical records of Holocene abrupt climate events, we particularly found that five centennial-scale wet events were broadly consistent with North Atlantic cooling events and a global synthesis of cold periods, supporting a ‘cold-wet’ climatic configuration in ACA. Analysis of the mechanisms responsible for these events suggests that these abrupt wet events in ACA were forced mainly by decreased sea surface temperatures (SSTs) in the North Atlantic and negative phases of the North Atlantic Oscillation (NAO). These changes resulted in strengthened mid-latitude cyclonic activity and delivered increased amounts of water vapor to ACA via the westerlies. Additionally, our identification of this ‘cold-wet’ configuration contrasts with the ongoing warming and wetting trend in ACA, and it provides a novel perspective for predicting long-term hydroclimatic changes in this region. Nevertheless, the uncertainty of our synthesis results owing to the limitations of currently available data should be considered and warrants verification in future studies. •First synthesis of Holocene centennial-scale climatic events in ACA, including five wet events and five dry events.•The intensified and southern-positioned westerlies favored the consistency of mega-regional abrupt events since ∼ 5.5 ka.•The ‘cold-wet’ climatic configuration under natural forcing differed from the recently ‘warm-wet’ trend in ACA.